دراسة القلق لدى لاعبي كرة لقدم اقل من 17 سنة أثناء المنافسة الرياضية - مغار فؤاد (My University, 2024)
ABSRACT : Thesistitle:study of anxiety in U17 football playersduring sports competitions. The studyaims to find out the main causes of anxiety and how to treatit, the extent to whichit affects the players’ performance, and helpingthemovercomesit by providingadequate information about it. Study problem:Doesanxiety have a negative impact on Under 17 football playersduringsportingcompetition? The partial hypothesizes: aplayer'snegative expectation of his performance and perception of failure, confusion and lack of concentration, or self-confidence and good preparation lead to good performance during sports competition for U17 footballers. Study sample:Some of the teams participating in Guelma State Championship and Annaba Regional Football League (100 playersfromdifferent teams). Researchmethodology: Descriptive-AnalyticalApproachusing questionnaire. Study Result: conduct training courses for coaches and organisers of sports competitions, allocate part of the training sessions to talk about the psychological aspect of playersduring sports competitions, and the need to assign training to profession people and specialistssincethey are aware of everythingthatsurrounds the playerfrom all aspects, especially the psychological aspect. ملخص :  عنوان الدراسة دراسة القلق لدى لاعبي كرة القدم أقل من 17 سنة أثناء المنافسة الرياضية.  هدف الدراسة معرفة أهم الأسباب المؤدية لظاهرة القلق أثناء المنافسة الرياضية وكيفية علاجها - مدى تأثير القلق على مستوى المنافسة الرياضية للاعبين اقل 17 سنة - مساعدة اللاعبين على تخطي ظاهرة القلق وذلك بتوفير القدر الكافي من المعلومات حول ظاهرة القلق  مشكلة الدراسة هل للقلق تأثير سلبي على لاعبي كرة القدم اقل من 17 سنة أثناء المنافسة الرياضية الفرضية الجزئية الأولى التوقع السلبي للاعب لمستوى أداءه وتصور الفشل تؤثر على أداءه أثناء المنافسة الرياضية الفرضية الجزئية الثانية الارتباك ونقص التركيز يؤثر على أداء لاعبي كرة القدم اقل من 17 سنة أثناء المنافسة الرياضية. الفرضية الجزئية الثالثة الثقة بالنفس والاستعداد الجيد يؤدي إلى أداء جيد أثناء المنافسة الرياضية للاعبي كرة القدم اقل 17 سنة.  عينة الدراسة بعض فرق ولاية قالمة المشاركة في البطولة الولائية لولاية قالمةورابطة عنابة الجهوية (100 لاعب من مختلف الفرق). المنهج المتبع في الدراسة تم استخدام المنهج الوصفي التحليلي. ادوات الدراسة استمارة الاستبيان  النتائج المتوصل إليها للقلق تأثير كبير على لاعبي كرة القدم اقل من 17 سنة أثناء المنافسة الرياضية إجراء تربص في دورات تكوينية لصالح المدربين والمنظمين للمنافسات الرياضية تخصيص جزء من الحصص التدريبية للتكلم على الجانب النفسي للاعبين أثناء المنافسة الرياضية ضرورة ايلاء التدريب لأشخاص ذو مستوى علمي وأصحاب التخصص لما لهم من دراية بكل ما يحيط باللعب من كل الجوانب خاصة الجانب النفسي. résumé : Titre de la thèse : étude de l'anxiété chez les joueurs de football de moins de 17 ans pendant les compétitions sportives. L'étude vise à découvrir les principales causes de l'anxiété et la manière de la traiter, la mesure dans laquelle elle affecte les performances des joueurs, et à les aider à la surmonter en leur fournissant des informations adéquates à ce sujet. Problème de l'étude : l'anxiété a-t-elle un impact négatif sur les joueurs de football de moins de 17 ans pendant les compétitions sportives ? L'hypothèse partielle est la suivante : l'attente négative d'un joueur quant à sa performance et la perception de l'échec, la confusion et le manque de concentration, ou la confiance en soi et une bonne préparation conduisent à une bonne performance des footballeurs de moins de 17 ans lors d'une compétition sportive. Échantillon de l'étude : Certaines des équipes participant au championnat de l'État de Guelma et à la ligue régionale de football d'Annaba (100 joueurs de différentes équipes). Méthodologie de recherche : Approche descriptive et analytique à l'aide d'un questionnaire. Résultat de l'étude : organiser des cours de formation pour les entraîneurs et les organisateurs de compétitions sportives, consacrer une partie des séances de formation à l'aspect psychologique des joueurs pendant les compétitions sportives, et la nécessité de confier la formation à des professionnels et à des spécialistes, car ils sont conscients de tout ce qui entoure le joueur sous tous ses aspects, en particulier l'aspect psychologique.
Keywords:  Anxiety;  Sports competition;  soccer;  القلق;  المنافسة الرياضية;  كرة القدم;  Anxiété;  Compétition sportive;  Football